A quantitative insight into metastatic relapse of breast cancer. (7th April 2016) - Hanin, Leonid; Pavlova, Lyudmila
Abstract: Background: Metastatic relapse is the principal source of breast cancer mortality. This work seeks to uncover unobservable, yet clinically important, aspects of post-surgery metastatic relapse of breast cancer and to quantify effects of surgery on metastatic progression. Methods: We classified metastases into three categories: (1) solitary cancer cells that were formed before or during surgery and either circulate in blood or are lodged at various secondary sites; (2) dormant or slowly growing avascular metastases; and (3) vascular secondary tumors. We developed a general mathematical model aimed at describing post-surgery dynamics of these three metastatic states. One parametric version of the model assumed that sojourn times of metastases in the three states are exponentially distributed while another was based on Erlang distribution. Model parameters were estimated from a sample of metastatic relapse or censoring times for 673 breast cancer patients treated with surgery. Results: We estimated the expected number of metastases at surgery and mean sojourn times for the three states and found that both are decreasing with state number. We also computed the probability that metastatic relapse resulted from a metastasis in a given state at surgery. The values of these attribution probabilities suggest that under the Erlang model all three states have a considerable effect on metastatic relapse while in the case of exponential model this is true for states 1 and 2 only. Conclusions: (1) In some patients metastasis occurred before surgery; (2) our results confirm significance of metastatic dormancy; (3) according to the model surgery stimulates escape from dormancy, promotes angiogenesis and accelerates metastatic growth in a fraction of breast cancer patients. Taken summarily, these findings call into question the benefits of primary tumor resection for certain categories of breast cancer patients. Highlights: A mathematical model of post-surgery dynamics of metastasis was developed. Model parameters were estimated from relapse time observations for 673 breast cancer patients. Metastasis in some patients occurred before detection of the primary breast tumor. Surgery stimulates escape from dormancy, promotes angiogenesis and boosts metastatic growth. Primary tumor resection may not be beneficial to certain categories of breast cancer patients.